Empirical evidence for the extent of spatial and temporal thermal variation on sea turtle nesting beaches - Holly Stokes (Journal of Thermal Biology, 2024)
Recording sand temperatures has become routine at many sea turtle nesting sites across the world given the impacts of incubation temperatures on hatchling sex ratios. However, the extent of thermal variability found at a nesting site has previously received little attention. Here we examine empirical sand temperature records across five atolls extending 250 km in the Chagos archipelago, Indian Ocean, between October 2012 and July 2023 and quantify the extent of spatial and temporal thermal variability. Our results suggest that sand temperatures at our study site vary seasonally and inter-annually, between beaches in the archipelago, and within beaches in different nesting habitats. The biggest drivers of thermal variability were seasonal and inter-annual differences, which modulated sand temperatures by up to 3.00°C and 1.03°C, respectively. Intra-beach and inter-beach variability further modulated temperatures by up to 0.56°C and 0.85°C, respectively. In addition, mean monthly sand temperatures were relatively low, suggesting that hatchling sex ratios are fairly balanced. The wide range of sand temperatures recorded at this nesting site suggests that it is likely both male-biased and female-biased clutches are produced during the nesting season. Quantifying thermal variability from a long-term sand temperature time series offers valuable insight into a population with temperature-dependent sex determination and, when possible, should be considered when modelling temperature impacts on hatchling sex ratios.